1992
DOI: 10.1259/0007-1285-65-775-594
|View full text |Cite
|
Sign up to set email alerts
|

Conventional 15 G needle technique for renal biopsy compared with ultrasound-guided spring-loaded 18 G needle biopsy

Abstract: Two techniques for percutaneous renal biopsy were retrospectively reviewed to assess their relative safety and efficacy. Ultrasound localization of the kidney by a radiologists, with subsequent biopsy performed by a renal physician using a hand-held 15 G cutting needle (Tru-Cut), was compared with biopsy performed by a radiologist using an 18 G cutting needle with a spring-loaded biopsy device (Biopty) and real-time ultrasound guidance. The smaller needle with real-time ultrasound is more reliable at retrievin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 8 publications
4
40
0
1
Order By: Relevance
“…A similar observation has been reported by other authors using needles of identical gauges [5]. The adequacy of the biopsy material also compared favorably with other reports in the literature [6,7,12] regardless of the technique used [5,13].…”
Section: Discussionsupporting
confidence: 88%
“…A similar observation has been reported by other authors using needles of identical gauges [5]. The adequacy of the biopsy material also compared favorably with other reports in the literature [6,7,12] regardless of the technique used [5,13].…”
Section: Discussionsupporting
confidence: 88%
“…There was a slightly larger proportion of complications using microbiopsy forceps, but it was not statistically significant [28]. There is paucity of studies focusing on the needle size, which is in contrast to studies in biopsies of other organs [29,30,31,32,33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…However, Wood et al [18] suggested that core biopsy and FNA are complementary and the combination of these techniques was better then either alone. Although complications are rare, it has been FNA CYTOLOGY FOR RENAL MASSES 15 shown that there is a lower complication rate when using ®ner needles for core biopsy [20], but this difference is not as clearly established in the kidney as it is for the liver. Theoretically therefore, FNA is probably a safer method of biopsy than needle-core biopsy, yet comparable in sensitivity.…”
Section: Discussionmentioning
confidence: 99%